Halal Tourism Marketing Strategies on Authentic Lombok Culture: A Preliminary Analysis - Ainul Yakin (Cordova Journal : languages and culture studies, 2020)
One of the very significant aspects affecting the satisfaction of the visitors on the intended destination is Halal tourism. Thus, the present study meant to examine Halal Tourism marketing strategies on authentic Lombok cultures, West Nusa Tenggara. A descriptive qualitative approach was utilized. The informers consisted of eight social-community prominent characters, and some representations of cultural advisors in Lombok Island. The instruments were digital camera, and recording devices. To collect the data, the observation, semi-structured interviews, and relevant documents were activated. The data was collected based on Miles’s and Huberman’s (1984) theory; data reduction, display, and conclusion. The finding exhibited that Halal Tourism marketing strategies on authentic Lombok culture is still low or not optimally attained. It was proved that local visitors (867,209) were higher than foreign visitors (583,621) in 2019 who came to Lombok Island.